ChemInform Abstract: Perovskite to Postperovskite Transition in NaFeF3. Issue 4 (January 2015) - Bernal, Fabian L.; Yusenko, Kirill V.; Sottmann, Jonas; Drathen, Christina; Guignard, Jeremy; Loevvik, Ole Martin; Crichton, Wilson A.; Margadonna, Serena
Abstract Polycrystalline samples of perovskite‐type NaFeF3 are prepared by solid state reaction of a 3:2:1 mixture of NaF, Fe, and FeF3 (Fe tube, 750 °C, 8 d).